Management of Technology Transfer in the Traditional Tempeh and Tofu Industries - Ign. Suharto; YIP Arry Miryanti; Lita Wijaya (Jurnal Kimia Terapan Indonesia, 2018)
The objective is to study the screening of Rhizopus sp inoculum, the utilization of this inoculum for a solid substrate soybean fermentation, to study the trial run of peeling machine and a fluidized bed reactor for the separation of soybean skin and soybean meat, to compare a manual cotton cloth bag filter and a manual rotary filter to separate soybean slurry, to run vertical technology transfer of a manual rotary filter into small scale tofu industry according to hygiene control and education skill training . The benefit of this research is to create a new business and to absorb manpower. The method used is a preparation of Rhizopus sp inoculum for fermentation. Trial run of the peeling machine and three phase fluidized bed reactor for the production of cleaned soybean. Cleaned soybeans are delivered to the production of a cake like fermented soybean , soy milk and tofu. Vertical transfer of technology of a manual rotary filter based on technometric approaches to soy milk and tofu industries. Education skill training was attended by 60 participants. The research results can be shown that the utilization of Rhizopus oligoporus and Rhizopus oryzae inoculum for soybean fermentation into a cake like fermented soybean can be accepted by the 60 panelists and local market. The trial run of peeling machine has a capacity of 30 kg per hour, the trial of three phase fluidized bed reactor can produce cleaned soybean after the total weight of soybean skin of about 35% from the total feed. Technology transfer of a manual rotary filter to the small scale of tofu industries can increase an efficiency of 66.37% for 25 minutes is better than a manual a cotton cloth bag filter with an efficiency of 62.62% for 36 minutes in tofu industry according to the hygiene control. This manual rotary filter can be scale-up into a larger scale. Education skill training was attended by 60 participants of a low income group people in rural areas in order to show how of the know how to do something better according to the hygiene control.